Analisis Implementasi Nilai-Nilai Education for Sustainable Development (ESD) pada SMA Negeri 1 Belitang - Rahma Aulia; Anisa Oktina Sari Pratama; Nur Hidayah (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
Education plays a strategic role in developing high-quality human resources while fostering awareness of environmental sustainability through the integration of Education for Sustainable Development (ESD) values in learning. This study aims to analyze the implementation of ESD values in the environmental aspect at SMA Negeri 1 Belitang, which was recognized as a National Adiwiyata School in 2023. This research employs a qualitative approach, with data collected through interviews, observations, questionnaires, and documentation. The data analysis techniques used include data reduction, data display, and conclusion drawing. The study evaluates 100 ESD indicators in the environmental aspect, revealing that 97 indicators (95%) have been successfully implemented. These include aspects of natural resources, climate change, as well as disaster prevention and mitigation. These activities have been integrated into the Merdeka Curriculum, both through classroom learning and school culture that promotes environmental awareness. However, there are still challenges, particularly the suboptimal implementation of disaster prevention and mitigation efforts. Therefore, the implementation of ESD at SMA Negeri 1 Belitang needs to be further improved to ensure it becomes more comprehensive, effective, and sustainable in the future.